ICARE_08_12_039 ... : [Paysages, voyages, bateaux, divers] ... - inconnu], [Photographe (NAKALA - https://nakala.fr (Huma-Num - CNRS), 2021)
Ours sur la banquise près de la mer [Duc d'Orléans] ... : Source: CNRS, UMR CReAAH, Archives, ICARE_PV0812039 ...